How do sex and sexual maturation influence the response of Monochamus galloprovincialis to host odours?. (13th February 2017) - Giffard, B.; David, G.; Joubard, B.; Piou, D.; Jactel, H.
Abstract: Finding the right host plant for feeding and reproduction is crucial for herbivorous insects. Usually they need both visual and olfactory cues to locate and colonize their host plants, but the respective role of the two types of stimuli is difficult to disentangle. Model plants mimicking the shape and colour of natural hosts, combined with odours dispensers, are relevant tools for this purpose. We used dummy pines and cut branches of natural pines to investigate host attraction in Monochamus galloprovincialis, the insect vector of the pine wood nematode in Europe. We compared the behavioural response of males and females, sexually mature or immature, in a large climatic chamber and in an olfactometer. Immature females were significantly attracted by the sole odours released by pines. Immature males and mature males and females needed a combination of visual and olfactory cues to find the host tree. These findings suggest that beetles use both visual and chemical cues to locate pine trees but that relevant stimuli likely differ between beetles of different sex and sexual maturation status. Our results question the implementation of precautionary clear‐cuts around infested trees for limiting the spread of PWN.